A Framework for the Testing and Validation of Simulated Environments in Experimentation and Training - Harris, David J.; Bird, Jonathan M.; Smart, Philip A.; Wilson, Mark R.; Vine, Samuel J. (Frontiers in Psychology, 2020)
New computer technologies, like virtual reality (VR), have created opportunities to study human behaviour and train skills in novel ways. VR holds significant promise for maximising the efficiency and effectiveness of skill learning in a variety of settings (e.g., sport, medicine, safety-critical industries) through immersive learning and augmentation of existing training methods. In many cases the adoption of VR for training has, however, preceded rigorous testing and validation of the simulation tool. In order for VR to be implemented successfully for both training and psychological experimentation it is necessary to first establish whether the simulation captures fundamental features of the real task and environment, and elicits realistic behaviours. Unfortunately evaluation of VR environments too often confuses presentation and function, and relies on superficial visual features that are not the key determinants of successful training outcomes. Therefore evidence-based methods of establishing the fidelity and validity of VR environments are required. To this end, we outline a taxonomy of the subtypes of fidelity and validity, and propose a variety of practical methods for testing and validating VR training simulations. Ultimately, a successful VR environment is one that enables transfer of learning to the real-world. We propose that key elements of psychological, affective and ergonomic fidelity, are the real determinants of successful transfer. By adopting an evidence-based approach to VR simulation design and testing it is possible to develop valid environments that allow the potential of VR training to be maximised.